2022
DOI: 10.1002/anie.202114786
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Zinc/Zeolite Catalyst: Selective Formation of p‐Xylene from Methanol to Aromatics Reaction

Abstract: The production of p-xylene from the methanol to aromatics (MTA) reaction is challenging. The catalytic stability, which is inversely proportional to the particle size of the zeolite, is not always compatible with p-xylene selectivity, which is inversely proportional to the external acid sites. In this study, based on a nano-sized zeolite, we designed hollow triple-shelled Zn/MFI single crystals using the ultra-dilute liquid-phase growth technique. The obtained composites possessed one ZSM-5 layer ( � 30 nm) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Combined with the difference of the acid type between SNZ-60 and NZ-240, the difference of aromatic selectivity further indicated that the high density of LAS on SNZ-60 played a positive role during the aromatic production. The introduction of Zn species could consume part of BAS on the surface, and the new generated Zn-LAS could obviously promote the dehydrogenation aromatization process of alkenes, the selectivity of total aromatics, and BTX could increase from 25.6 and 14.1% to 34.5 and 18% of NZ-60, respectively . In addition, the selectivity of light alkanes was significantly decreased from 27 to 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the difference of the acid type between SNZ-60 and NZ-240, the difference of aromatic selectivity further indicated that the high density of LAS on SNZ-60 played a positive role during the aromatic production. The introduction of Zn species could consume part of BAS on the surface, and the new generated Zn-LAS could obviously promote the dehydrogenation aromatization process of alkenes, the selectivity of total aromatics, and BTX could increase from 25.6 and 14.1% to 34.5 and 18% of NZ-60, respectively . In addition, the selectivity of light alkanes was significantly decreased from 27 to 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolitic core–shell structures often provide versatile beneficial functions for catalysis, , for instance, shape selectivity, , bifunctionality, and sintering resistance. , Rimer et al have developed abundant types of core–shell and egg-shell zeolite catalysts that showed enhanced performance in hydrocarbon processing as well as biomass conversion. , Very recently, the core–shell zeolite has also been reported for CO 2 conversion, primarily for the regulation of the selectivity of aromatic products. , Herein, we report that such a core–shell zeolite structure was able to overcome the challenges aforementioned during CO 2 hydrogenation, where the construction of the shell, referring to coating a layer of silicalite-1 (S-1) over a pristine zeolite H-ZSM-5 crystal, was realized by a facile secondary growth. Such an S-1 shell was found to be able to secure the bifunctional nature of a typical CO 2 hydrogenation catalyst, i.e ., In 2 O 3 /H-ZSM-5, by which the activity for the synthesis of C 2 + hydrocarbons under both nanoscale (in a manner of PM) and microscale (in a manner of GM) proximity was well-improved.…”
Section: Introductionmentioning
confidence: 82%
“…Additionally, zeolite coking could be another potential deactivation factor for such an MTH-involved bifunctional catalysis process in practical application scenarios, 31,38 although during CO 2 hydrogenation, long-term (∼100 h) stability was usually observed in lab-scale research. 18,27 Zeolitic core−shell structures often provide versatile beneficial functions for catalysis, 39,40 for instance, shape selectivity, 41,42 bifunctionality, 43 and sintering resistance. 44,45 Rimer et al have developed abundant types of core−shell and egg-shell zeolite catalysts that showed enhanced performance in hydrocarbon processing as well as biomass conversion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the MTP process have shown that small-pore zeolites with weak acidity show promise as catalysts for the olefin-based catalytic cycle and can increase the propene yield. The MTA process can also efficiently produce aromatics [148,149] that are very important platform molecules for high-value commodity chemicals [150] . Although the MTA reaction was not addressed in detail in this review, highly acidic zeolites having large pore channels may be able to promote this reaction based on prior research regarding the dual cycle mechanism.…”
Section: Discussionmentioning
confidence: 99%